The Role of Quasi-Logical Arguments in Critical Dialogue: A Pragma-Dialectical Redefinition - Iva Svačinová (Informal Logic, 2017)
The article focuses on the New Rhetoric’s concept of quasi-logical arguments imitating logical or mathematical demonstrations, and examines it from point of view of pragma-dialectics as a device contributing towards resolving the difference of opinion. It is shown that the category of quasi-logical arguments cannot be considered as an argument scheme or a united type of strategic maneuvering. It is suggested to consider the category of quasi-logical arguments as a cluster of specific strategic maneuvers increasing the efficiency of arguments under certain circumstances. This approach is demonstrated in a case study of pragma-dialectical analysis of the quasi-logical scheme of probability.